Usefulness of Point-Of-Care Ultrasound in Diagnosing and Managing Pediatric Multidistrict Chylous Effusion - Tommaso Bellini; Marta Bustaffa; Marco Crocco; Federica Casabona; Giorgia Iovinella; Federica Malerba; Matteo D’Alessandro; Emanuela Piccotti (Reports)
Background and Clinical Significance: The use of point-of-care ultrasound (POCUS) in emergency departments is rapidly growing due to its ability to provide immediate and accurate diagnostic information at the bedside. Furthermore, it can provide precise and rapid information on the location of multidistrict effusions in patients with suspected lymphatic decompensation. Case Presentation: This unique clinical case report describes a patient who presented with massive, multidistrict chylous effusion secondary to acute lymphatic insufficiency, a rare and challenging condition. Due to a recent diagnosis of celiac disease, the patient had started a gluten-free diet ten days before the onset of symptoms, suggesting a possible causal link. Through comprehensive thoracoabdominal POCUS, the diagnosis was made promptly, avoiding delays in treatment and enabling timely decision-making. Conclusions: This case emphasizes the critical role of POCUS not only in expediting diagnosis but also in guiding invasive procedures, such as thoracentesis, by visualizing fluid accumulation and anatomical structures in real-time. Moreover, POCUS provides an invaluable tool for ongoing clinical ultrasound follow-up, facilitating continuous monitoring without exposing the patient to the risks of radiation, thus optimizing patient care and resource utilization.